1985
DOI: 10.1093/oxfordjournals.aje.a113979
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Heart Disease: Prevalence at Livebirth

Abstract: The Baltimore-Washington Infant Study is a regional epidemiologic study of congenital heart disease. Among Infants born in the study area in 1981 and 1982, 664 had a diagnosis of congenital heart disease confirmed in the first year of life by echocardiography, cardiac catheterization, cardiac surgery, or autopsy. The prevalence rate was 3.7/1,000 livebirths for all cases and 2.4/1,000 livebirths for cases confirmed by invasive methods only. Diagnosis-specific prevalence rates of congenital heart disease are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
485
6
28

Year Published

1987
1987
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 931 publications
(539 citation statements)
references
References 0 publications
20
485
6
28
Order By: Relevance
“…The rates of specific cardiac defects in our study are generally comparable with 186 those reported from the Baltimore-Washington study by Ferencz et al and from EUROCAT registry [1,6,7]. As 187 expected, the most frequent diagnosis was ventricular septal defect, followed by atrial septal defect, patent 188 arterial duct, pulmonary stenosis, and atrioventricular septal defects.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…The rates of specific cardiac defects in our study are generally comparable with 186 those reported from the Baltimore-Washington study by Ferencz et al and from EUROCAT registry [1,6,7]. As 187 expected, the most frequent diagnosis was ventricular septal defect, followed by atrial septal defect, patent 188 arterial duct, pulmonary stenosis, and atrioventricular septal defects.…”
supporting
confidence: 85%
“…The rate for atrioventricular septal defect is 4.3%, mean 196 percentage with regards to reports from other registries with rates from 1.34% to 7.4% [6,33]. Incidence of 197 atrioventricular septal defects varies in accordance with the age of the involved mothers due to fact that the 198 Down syndrome is more common in mothers who are more than 34 years old, and atrioventricular septal defects 199 are very frequent in those with Down syndrome [5,13].…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Congenital heart diseases (CHD) are relatively common with a prevalence ranging from 3.7 to 17.5 per 1000 live births (1,2). According to a status report on CHD in India, 10% of the present infant mortality may be accounted for by CHD (3).…”
Section: Introductionmentioning
confidence: 99%
“…Morbidity and mortality of laterality defects are generally attributed to associated complex congenital heart defects (CHDs), suggesting that the developing heart is particularly susceptible to disturbances in LR patterning (Kathiriya and Srivastava, 2000). Individuals with situs inversus have a higher incidence of CHDs than individuals with normal LR development (ϳ3% vs. Ͻ0.1%), whereas ϳ90% of individuals with heterotaxia or isomerism are estimated to show complex CHDs (Ferencz et al, 1985;Bowers et al, 1996;Freed, 2001;Walmsley et al, 2004;Ramsdell, 2005). Cardiac malformations most commonly associated with LR patterning defects include atrial and ventricular septal defects, single (common) ventricle, transposition of the great arteries, double-outlet right ventricle (DORV), and pulmonary stenosis or atresia (Freed, 2001).…”
Section: Introductionmentioning
confidence: 99%